Penerapan Fuzzy C-Means Untuk Penentuan Besar Uang Kuliah Tunggal Mahasiswa Baru - Muchsin, Ariyady Kurniawan; Sudarma, Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.3 Desember 2015DO - 10.24843/LKJITI.2015.v06.i03.p04, 2015)
In accordance with the mandate of the 1945 Constitution article 31 concerning the education authorities have issued various policies to realize the cost of education is getting cheaper and affordable to all people, one of which is the system UKT (Tuition Single) which is partially Tuition Single (BKT) which were passed to each student based on their economic capabilities. UKT grouping mechanism is still done manually by Udayana University which resulted in the value of equity for prospective new students to their economic capacity is still lacking. Therefore, it needs a mechanism for charging and determination UKT which can be done online, so as to improve efficiency and effectiveness. The next solution that can be done is by using classification techniques using Fuzzy C-Means (FCM) and Beni Xie Index to determine the optimum clusters in the process of determining the type UKT so as to meet the values ??of justice for prospective new students.